2018
DOI: 10.1159/000492996
|View full text |Cite
|
Sign up to set email alerts
|

Local Delivery of β-Elemene Improves Locomotor Functional Recovery by Alleviating Endoplasmic Reticulum Stress and Reducing Neuronal Apoptosis in Rats with Spinal Cord Injury

Abstract: Background/Aims: Spinal cord injury (SCI) is a serious global problem that leads to permanent motor and sensory deficits. This study explores the anti-apoptotic and neuroprotective effects of the natural extract β-elemene in vitro and in a rat model of SCI. Methods: CCK-8 assay was used to evaluate cell viability and lactate dehydrogenase assay was used to evaluate cytotoxicity. A model of cell injury was established using cobalt chloride. Apoptosis was evaluated using a fluorescence-activated cell sorting ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…It is well known that the secondary injury caused by SCI induces neuronal cell death [7]. Furthermore, this neuronal cell death largely results in injured axons, which is difficult for them to regenerate and reestablish connections with the other neurons during injury [8].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the secondary injury caused by SCI induces neuronal cell death [7]. Furthermore, this neuronal cell death largely results in injured axons, which is difficult for them to regenerate and reestablish connections with the other neurons during injury [8].…”
Section: Introductionmentioning
confidence: 99%
“…Thirty days after SCI, CHOP expression was increased in the remaining white matter, suggesting that CHOP is involved in ER stress-mediated apoptosis. The misfolded proteins accumulated abnormally, causing the Caspase-12/Caspase-3 activation and upregulated expression of GRP78, which subsequently leads to cell apoptosis, after the occurrence of ER stress (Wang et al, 2018;Li et al, 2019b). Our study found that CAT could effectively inhibit the expressions of Caspase-12/Caspase-3 and GRP78 and reduce cell apoptosis in the SCI.…”
Section: Discussionmentioning
confidence: 56%
“…The second advantage of β-elemene in neuropathic pain management is its potential neuroprotective activity, since β-elemene could promote locomotor behavioural recovery by reducing neural apoptosis and enhancing neural regeneration in rats with spinal cord injury. 48 , 49 Clinical data demonstrated that compared with chemotherapeutic drugs, β-elemene had fewer side effects, including heart, liver, kidney and bone marrow damage. 50 In this study, neither locomotor disturbance nor liver and kidney injury were observed in rats.…”
Section: Discussionmentioning
confidence: 99%